Factors Associated with Pulmonary Tuberculosis and Latent Tuberculosis Infection of Household Contacts with Drug-Sensitive Tuberculosis Patients in Medan - Rina Sundari; Bintang Yinke Magdalena Sinaga; Delores Elisabeth Sormin; Arlinda Sari Wahyuni (Public Health of Indonesia, 2026)
Background: Latent Tuberculosis Infection (LTBI) has the potential to develop into active TB. Therefore, appropriate diagnosis and management are essential, especially in high-risk populations such as individuals who are in household contact with active TB patients. Objectives: To analyze the factors associated with pulmonary tuberculosis and latent tuberculosis infection (LTBI) in household contacts with drug-sensitive tuberculosis patients in Medan Methods: This research is an observational analytical with a cross-sectional design conducted in several health facilities in Medan for 4 months. This study included 105 household contacts from 67 index cases who were diagnosed with drug-sensitive TB, confirmed by Xpert MTB/RIF examination. Statistical analysis used the Chi-Square test with a p-value <0.05 were considered significant. The study used odds ratios and 95% confidence intervals to analyze how associated factors are linked to TB infection. Results: Among 105 household contacts with drug-sensitive TB patients, 31 people (29.6%) had latent TB infection, and 11 people (10.5%) had pulmonary TB infection. In bivariate analysis we found that the variable associated with pulmonary TB was alcohol consumption (OR 20.6677; CI 95% 1.703-250.782; p=0.028). In household contacts with TB patients, no statistically significant factors associated with latent TB infection were found (p>0.05). Conclusion: In household contacts with drug-sensitive TB patients, alcohol consumption are 20.667 times more at risk of experiencing pulmonary TB than those who do not consume alcohol. However, no significant associated factors for latent TB infection were found.